Borderline conditions for single or platooning operations in freight transport on expressways: Case study in Japan - Kawasaki, Tomoya; Tagawa, Hoshi; Lau, Yui-yip (Frontiers in Future Transportation, 2022)
Truck platooning is defined as a convoy of freight vehicles operated using an electronic coupling system, and has several advantages, particularly in terms of cost savings for fuel consumption and labor. Platooning technology is introduced by discussing several issues: the distance between trucks, number of trucks convoyed, waiting time at the platooning center, and distance between the origin and destination, all of which are variables that influence the transport costs. Important is to identify the extent to which these factors affect borderline conditions for single or platooning freight transport operations. Therefore, this study aims to develop a cost function of platooning operations, compare transport costs between single and platooning operations, determine the factors that affect the transport costs and identify the borderline conditions for single or platooning operations. The cost functions in the hypothetical network were developed by considering the important factors that contribute to the transport costs in Japanese road freight transport. A scenario analysis was conducted to investigate the impact of the inter-vehicle distance and the number of platooned trucks on the borderline conditions. Our results revealed that the platooning operation would offer a comparative advantage with a shorter inter-vehicle distance. For example, for an inter-vehicle distance of 49 m and a distance of 800 km between the origin and destination, the platooning operation is not advantageous compared with manned driving unless the waiting time at the platooning center is less than 30 min. In addition, a platooning operation is feasible even with a travelling distance of 100 km if the trailing vehicles are unmanned. The highest cost contributor is the cost of labor, the reduction of which can significantly reduce the total transport costs.